THE EFFECT OF PICTURE AND PICTURE MEDIA IN WRITING PROCEDURE TEXT ON NINTH GRADE STUDENTS OF SMP N 1 TEBING TINGGI - David Gordon Gultom; Mungkap Mangapul Siahaan; Leonita Maria Efipanias Manihuruk (EDUTECH, 2024)
The object of this research was to determine the effect of picture and picture media in writing procedure text on ninth grade students at SMP N 1 Tebing Tinggi. This research focuses on the effect of using picture media to help students write procedure text with the theme about how to make a cup of coffe. This research used quantitative research with a quasi-experimental research design. The population of this study was the grade ninth students of SMP N 1 Tebing Tinggi with a total of 297 students. The sample of this study was divided into two classes, namely the experimental class (IX 4) consist of 33 students who used the picture and picture media and the control class (IX 2) consist of 33 students who used the conventional media (textbooks). Data collection instruments used writing tests for pre-test and post-test. H. Douglas Brown’s writing assessment rubric was used this research, which includes several aspects: content, organization, syntax, vocabulary, and mechanics. The alpha formula was used to analyze the data, by conducting descriptive analysis. The result of data analysis using the arikunto formula that the value of 6,63 1,669. Based on these findings, Ha was accepted and Ho was rejected. Therefore, it can be concluded that the picture and picture media significantly affects the students writing at SMP N 1 Tebing Tinggi in writing procedure text.